UNCOVERING THE RELATIONSHIP BETWEEN 7 STRESS FACTORS OF SV-NBJSQ INDONESIAN VERSION AND JOB STRESS ON EMPLOYEE IN GREATER JAKARTA & BANDUNG - Rabbani, Ghazali Akmal; Novani, Santi (Ridwan Institute, 2024)
This study investigates the relationship between seven stress factors identified by the Short Version-New Brief Job Stress Questionnaire (SV-NBJSQ) Indonesian version and overall job stress among employees in Greater Jakarta and Bandung. The research design is structured to systematically gather, analyze, and interpret data to address the study's research questions, which aim to identify significant stress factors and develop an objective model for calculating and categorizing stress levels. The data analysis involved two main components: calculating the Stress Index and classifying stress levels, followed by analyzing the structural relationships between the seven factors and job stress using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The research found that depression symptoms are the most significant predictor of job stress, while physical reactions, anxiety symptoms, and fatigue symptoms also showed positive but lesser correlations. Moreover, the research validated the use of the SV-NSQ in Indonesia, providing a localized tool for assessing job stress.